Growth, patterning and alignment of organolead iodide perovskite nanowires for optoelectronic devices1. Issue 9 (4th March 2015) - Deng, Hui; Dong, Dongdong; Qiao, Keke; Bu, Lingling; Li, Bing; Yang, Dun; Wang, Hong-En; Cheng, Yibing; Zhao, Zhixin; Tang, Jiang; Song, Haisheng
<x xml:space="preserve">Abstract</x> Organolead halide perovskite nanowires are becoming intriguing materials applied in optoelectronics.